2016
DOI: 10.1158/1055-9965.epi-15-0819
|View full text |Cite
|
Sign up to set email alerts
|

Overdiagnosis in Mammographic Screening because of Competing Risk of Death

Abstract: Background: Different definitions and estimates of overdiagnosis in mammographic screening reflect a substantial need to investigate and understand the complexity of the issue. This modeling study aims to estimate the number of overdiagnosed women, defined as those diagnosed with breast cancer who die from any cause within the lead-time period.Methods: We used numbers from incidence and death statistics available online and published estimates of lead-time. Postulated cohorts of screened and not screened women… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…This study reported the frequency of overdiagnosis among a cohort of women over a period of 10 years after they participated in cancer screening. Falk et al estimated the number of women overdiagnosed in mammographic screening using English, Welsh, and Norwegian data (Falk et al, 2016). Moreover, Kilpeläinen et al, (2016) reported the association of prostate cancer with socioeconomic status in Finland.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported the frequency of overdiagnosis among a cohort of women over a period of 10 years after they participated in cancer screening. Falk et al estimated the number of women overdiagnosed in mammographic screening using English, Welsh, and Norwegian data (Falk et al, 2016). Moreover, Kilpeläinen et al, (2016) reported the association of prostate cancer with socioeconomic status in Finland.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, the risk of overdiagnosis due to competing risk of death is thought to be less than 2%. 33 This paper thus limits its scope to discussing the former cause of overdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a modeling study using data from England and Norway, Falk and Hofvind estimated that in a population offered screening, between 2% and 4% of women diagnosed with breast cancer would die from other causes within the estimated lead-time. 34 Owing to the reduced life expectancy, we expect this inevitable proportion of overdiagnosed breast cancer cases to be larger in women with than in women without chronic diseases.…”
Section: Discussionmentioning
confidence: 99%